2017
DOI: 10.1111/cea.13063
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of allergic sensitization and atopic dermatitis from 1 to 3 years: Effects on allergic diseases

Abstract: SummaryBackground: While allergic sensitization and atopic dermatitis (AD) are known to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 36 publications
3
54
3
3
Order By: Relevance
“…2 Compared to this study, the age-matched CHILD study reported sensitization only by SPT; however, the major allergen sources were consistent between these two Canadian cohorts. 2 Compared to this study, the age-matched CHILD study reported sensitization only by SPT; however, the major allergen sources were consistent between these two Canadian cohorts.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…2 Compared to this study, the age-matched CHILD study reported sensitization only by SPT; however, the major allergen sources were consistent between these two Canadian cohorts. 2 Compared to this study, the age-matched CHILD study reported sensitization only by SPT; however, the major allergen sources were consistent between these two Canadian cohorts.…”
contrasting
confidence: 57%
“…2 The same set of SPT solutions was used in both studies. 2 The same set of SPT solutions was used in both studies.…”
mentioning
confidence: 99%
“…Except at 3 to 7 years of age, atopic dermatitis was positively associated with prescriptions of ICS, but low RRs suggest that atopic dermatitis had little impact, as also reported by others . Lower prevalence of atopy than LRTI and wheeze (18‐36 months), can partly explain the low AAFs particularly for allergic rhinoconjunctivitis (18‐36 months), although there were moderately associations.…”
Section: Discussionmentioning
confidence: 57%
“…A child was considered to be sensitised if SPT showed ≥2 mm wheal to any of 4 foods (peanut, milk, egg white or soy) or 13 inhalants (alternaria tenuis, cat hair, dog epithelium, house dust mites (Der.p and Der.f), cockroach, penicillium, cladosporium, aspergillus fumigatus, trees, grasses, weeds and ragweed). Details of skin tests procedure have been described previously …”
Section: Methodsmentioning
confidence: 99%